2015
DOI: 10.5737/23688076253335340
|View full text |Cite
|
Sign up to set email alerts
|

An integrative framework to support the assessment function of Quebec’s pivot nurses in oncology

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Among the four NN functions, patient assessment showed the lowest ratings, which might be explained by the complexity of assessment/evaluation activities in cancer care (Hébert & Fillion, 2011;Hryniuk et al, 2014;Fournier et al, 2015). In response to existing gaps in assessment (e.g., oncology referrals, delays in treatment), a pilot study by Zibrik et al (2016) tested the benefit of the NN integration into the triage process for patients with cancer and found that early NN care involvement improved timely patient assessment, resource utilization and optimal treatment delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four NN functions, patient assessment showed the lowest ratings, which might be explained by the complexity of assessment/evaluation activities in cancer care (Hébert & Fillion, 2011;Hryniuk et al, 2014;Fournier et al, 2015). In response to existing gaps in assessment (e.g., oncology referrals, delays in treatment), a pilot study by Zibrik et al (2016) tested the benefit of the NN integration into the triage process for patients with cancer and found that early NN care involvement improved timely patient assessment, resource utilization and optimal treatment delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Des quatre fonctions des infirmières pivots, l'évaluation des patients a reçu la note la plus faible; ce résultat est sans doute attribuable à la complexité des activités d'évaluation dans les soins du cancer (Hébert et Fillion, 2011;Hryniuk et al, 2014;Fournier et al, 2015). Pour pallier les écarts existants dans l'évaluation (p. ex.…”
Section: Discussionunclassified